Hussein AL-Husseiny and his Politilcal Role in Lebanon (1968-1992) (Journal of the College of Education for Women, 2019)
The study of the historical figures is one of the important in modern history since it is main focus is to show the political , economic or social product of a specific person throughout his life . Therefore , the subject of my research is “ Hussein AL-Husseiny and his politilcal role in Lebanon1968-1992. The research focused on high highting his role in Lebanon within the parliament and the ministry , he has help for the duration of the study. It also dealt with his national attitudes which he lived toward most of crucial issues in Lebanon